Analysis of sediment quality in the Port of Rio de Janeiro channel: Considerations about collection methods indicated by Brazilian resolutions - Bertoni, Fabiane; Senez-Mello, Thaise; Oliveira Filho, Silvio Roberto; Crapez, Mirian Araújo Carlos; Fonseca, Estefan Monteiro (Quaternary and Environmental Geosciences, 2023)
The environmental impacts caused by dredging and disposal of the removed sediment may cause direct and indirect effects on ecosystems and organisms. Therefore, dredging activities in Brazilian ports must follow the requirements of the regulations established by the national environmental council (with the Portuguese acronym CONAMA) in order to standardize the characterization of the sedimentary package of the area to be dredged. According to CONAMA Resolution 454/2012, two different sampling methods can be used: simple sampling or composite sampling. This study aims to analyze the results of both sediment sampling methods in the same area, through the analysis of the concentration of contaminants in the samples, to contribute to the discussion of the methodological choice of environmental quality monitoring that best suits the Brazilian context. For this purpose, two sediment sampling campaigns were carried out in the navigation channel of the Port of Rio de Janeiro, in Guanabara Bay (RJ). In the first and second campaigns, the simple and composite methods were employed respectively. The concentration of contaminants was analyzed considering firstly the different individualized variables and then correlation of the variables, using the principal component analysis (PCA). The simple sampling showed concentrations, in general, higher than the composite sampling. The principal component analysis indicates a correlation between metals, aromatic polycyclic hydrocarbons and total organic carbon, for both sampling methods, however, it exhibits the highest concentrations in the sample collected using the simple method. The concentrations of total nitrogen and total phosphorus showed a correlation with sedimentation related to the greater presence of fine sediments. It was found that the simple method better preserves the characteristics of the samples, thus being more compatible with the represented environment.